2021
DOI: 10.1590/1983-21252021v34n418rc
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Nature of Water and Hydrogen Peroxide on the Formation of Passion Fruit Seedlings1

Abstract: This study was carried out with the objective of evaluating the water relations, photosynthetic pigments and growth of passion fruit cv. BRS Rubi do Cerrado, as a function of the cationic nature of irrigation water and exogenous application of hydrogen peroxide. The experiment was carried out under greenhouse conditions in Pombal – PB, Brazil. The experimental design was randomized blocks, in a 6 × 4 factorial scheme, corresponding to six cationic nature of water - CNW (S1 - Control; S2 - Na+; S3 - Ca2+; S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…It is important to highlight that, despite the reduction in DQI, plants subjected to ECw of 4.3 dS m -1 (Na + ; Ca 2+ ; Na + +Ca 2+ ; Mg 2+ , and Na + +Ca 2+ +Mg 2+ ) were suitable to be transplanted to the field, because they had DQI higher than 0.20, being considered seedlings of acceptable quality for transplanting to the field (DICKSON; LEAF; HOSNER, 1960). Lima et al (2021a) evaluated the quality of passion fruit seedlings, cv 'BRS Rubi do Cerrado', as a function of the cationic nature of irrigation water and observed that, although there was a reduction in the DQI, regardless of the cationic nature, the use of water with electrical conductivity of 3.0 dS m -1 led to the production of seedlings with Dickson quality index higher than 0.2, considered acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to highlight that, despite the reduction in DQI, plants subjected to ECw of 4.3 dS m -1 (Na + ; Ca 2+ ; Na + +Ca 2+ ; Mg 2+ , and Na + +Ca 2+ +Mg 2+ ) were suitable to be transplanted to the field, because they had DQI higher than 0.20, being considered seedlings of acceptable quality for transplanting to the field (DICKSON; LEAF; HOSNER, 1960). Lima et al (2021a) evaluated the quality of passion fruit seedlings, cv 'BRS Rubi do Cerrado', as a function of the cationic nature of irrigation water and observed that, although there was a reduction in the DQI, regardless of the cationic nature, the use of water with electrical conductivity of 3.0 dS m -1 led to the production of seedlings with Dickson quality index higher than 0.2, considered acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being considered a fruit species of significant importance to Northeastern Brazil, this region shows limitations for the expansion of irrigated agriculture due to low rainfall rates and high evapotranspiration, resulting in a water scarcity scenario that forces producers to use underground water sources with high salt contents (Veloso et al, 2018). Furthermore, the chemical nature of these water bodies is diversified and influenced by factors such as regional climatic conditions, the mineralogical composition of rocks, water residence time, and the underground water flow (Lima et al, 2016;Silva et al, 2018a;Lima et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%